Attitudes and Perceptions of Health Protection Measures Against the Spread of COVID-19 in Italy and Poland - Lorettu, Liliana; Mastrangelo, Giuseppe; Stepien, Joanna; Grabowski, Jakub; Meloni, Roberta; Piu, Davide; Michalski, Tomasz; Waszak, Przemyslaw M.; Bellizzi, Saverio; Cegolon, Luca (Frontiers in Psychology, 2021)
Background: During the first wave of the COVID-19 pandemic (April to May 2020), 6,169 Polish and 939 Italian residents were surveyed with an online questionnaire investigating socio-demographic information and personality traits (first section) as well as attitudes, position, and efficacy perceptions on the impact of lockdown (second section) and various health protection measures enforced (third section). Methods: The “health protection attitude score” (HPAS), an endpoint obtained by pooling up the answers to questions of the third section of the survey tool, was investigated by multiple linear regression models, reporting regression coefficients (RC) with 95% confidence intervals (95% CI). Results: Concerns for business and health due to COVID-19 were associated with a positive attitude toward risk reduction rules. By contrast, male sex, concerns about the reliability of information available online on COVID-19 and its prevention, along with the feeling of not being enough informed on the transmissibility/prevention of SARS-CoV-2 were associated with a negative attitude toward risk mitigation measures. Discussion: A recent literature review identified two social patterns with different features in relation to their attitude toward health protection rules against the spread of COVID-19. Factors positively associated with adherence to public health guidelines were perceived threat of COVID-19, trust in government, female sex, and increasing age. Factors associated with decreased compliance were instead underestimation of the COVID-19 risk, limited knowledge of the pandemic, belief in conspiracy theories, and political conservativism. Very few studies have tested interventions to change attitudes or behaviors. Conclusion: To improve attitude and compliance toward risk reduction norms, a key intervention is fostering education and knowledge on COVID-19 health risk and prevention among the general population. However, information on COVID-19 epidemiology might be user-generated and contaminated by social media, which contributed to creating an infodemic around the disease. To prevent the negative impact of social media and to increase adherence to health protection, stronger content control by providers of social platforms is recommended.